Older adults do not consistently overestimate their action opportunities across different settings - Isabel Bauer; Milena S. Gölz; Lisa Finkel; Maddalena Blasizzo; Sarah E. M. Stoll; Jennifer Randerath (Scientific Reports)
Abstract Am I still able to climb the ladder? Aging accompanies changes in physical constitution and a higher risk of injuries. At the same time, the judgment of action opportunities needs to be highly adaptive to the given task setting. We examined older adults’ (n = 40) judgment tendencies in four different tasks by use of a detection theory approach. The tasks’ setting differed in their boundaries’ proximity to the actor with either proximal (e.g., judging one’s hand fit into an opening) or distal boundaries (e.g., judging the reachability of a distant object). The older participants showed significantly more liberal judgments in tasks with distal boundaries. Body awareness and alertness were associated with the extent of judgment disparity between setting types. Subsequently, we compared a gender- and education-matched subsample of the group (n = 24) to a younger sample (n = 24). Older participants’ judgment tendencies were significantly more extreme, with stronger under- or overestimations depending on the type of setting. We discuss potential links between more extreme judgments in older adults and higher reliance on learned patterns. Future research is needed to further unravel these setting-dependent behavioral differences and the factors contributing to more extreme judgment tendencies with growing age.